An Analysis of the Quality of Service Provided by Sayang Warga Application in the Sukolilo District Office, Surabaya - Paulus Magnus Nagus; Amirul Mustofa; Ulul Albab (International Journal of Scientific Multidisciplinary Research, 2023)
The purpose of this study is to determine the quality of population administration services at the Sukolilo District Office in Surabaya. Population administration services are a continuous series of structuring and controlling activities, as well as the issuance of documents and population data. Quality public services will increase citizen satisfaction and demonstrate the validity of population management. The descriptive qualitative method was used in this study, with the first research instrument being the researcher himself, who collects, manages, analyzes, interprets, and verifies all data and information obtained from participant observation of every setting and event. Primary and secondary data were gathered through interviews, observations, and literature searches. The findings revealed that the quality of population administration services provided by the Sayang Warga website in Sukolilo District is optimal, with the fifth dimension of service quality dimensions, namely Tangibles, Reliability, Responsibility, Assurance, and Empathy, running optimally and conducively. According to the research, many Sukolilo District residents have used the Sayang Warga website to complete and manage the necessary data or files, which is supported by the graphic data that the researcher has presented